A fast, efficient and high-concentration fluorine-doped zinc oxide preparation method

Through the combination of femtosecond laser and fast annealing, the problems of low -doping zinc oxide doping and complex response in existing technologies have been solved. Electronic migration rate and transparency, and avoiding decreased device performance.

CN116239141BActive Publication Date: 2025-01-28NANKAI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310224534.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2025-01-28
Estimated Expiration
2043-03-09

Smart Images

  • Figure CN116239141B_ABST
    Figure CN116239141B_ABST
Patent Text Reader

Abstract

The present invention provides a fast, efficient, high-concentration fluorine-doped zinc oxide preparation method, the method comprising the following steps: placing a zinc oxide sample on a three-dimensional translation stage of a vacuum chamber; introducing doping gas into the chamber; irradiating the sample surface with a femtosecond laser to achieve high-concentration fluorine doping; annealing the doped zinc oxide sample to activate the fluorine impurity atoms in the material, while repairing the lattice and eliminating defects, thereby obtaining high-concentration fluorine-doped zinc oxide; the zinc oxide treated by the above steps has a high impurity doping concentration, and the relative atomic ratio of fluorine can reach more than 9at.%. The method is fast, efficient, and can achieve the preparation of high-concentration fluorine-doped zinc oxide without complex chemical reactions. By doping non-metallic elements, electron scattering in the conduction band is greatly reduced, thereby improving carrier mobility and optical transmittance, and can effectively improve the current carrying capacity of zinc oxide-based devices and reduce device power consumption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of doped ZnO preparation, and in particular to a method for preparing fast, efficient and high-concentration fluorine-doped zinc oxide. Background Art

[0002] Transparent conductive oxide (TCO) films are important optoelectronic materials. Due to their high optical transparency and excellent electrical conductivity, they have been widely studied and applied in optoelectronic devices such as thin-film solar cells, flat-panel liquid crystal displays, and light-emitting diodes. As we all know, the most commonly used TCO film is indium tin oxide (ITO) because of its high transparency and electrical conductivity. However, indium is toxic and its content on earth is limited, which has prompted researchers to look for other alternative materials. Among the possible alternative materials, zinc oxide (ZnO) is considered to be the most promising candidate to replace ITO because it has similar optoelectronic properties to ITO, lower cost, non-toxicity, and high chemical stability under hydrogen plasma. However, the carrier concentration in intrinsic ZnO is very low at room temperature and is very sensitive to temperature changes, making it difficult to control the properties of this semiconductor. In the past few decades, doping has been a very effective means to solve these problems. For example, ZnO films doped with cations such as Al and Ga have high carrier concentrations and low resistivity. However, in relative ionic semiconductors such as ZnO, the conduction band mainly comes from the metal (Zn) orbit. Therefore, each added metal atom produces a strong local perturbation to the conduction band, leading to strong electron scattering within the conduction band. In addition, the increase in the number of carriers leads to higher free carrier absorption. Therefore, the high concentration of carriers in metal-doped ZnO films limits the carrier mobility and optical transparency, reduces the current carrying capacity of ZnO-based devices, and greatly increases power consumption.

[0003] In recent years, it has been reported that non-metallic doping may be a more suitable strategy for obtaining high-quality TCO films. This is because the electron perturbations caused by non-metallic dopants are largely confined to the filled valence band, thereby reducing the scattering of conduction band electrons, which in turn can achieve higher electron mobility and transparency. Among the possible non-metallic dopants, fluorine (F) is a promising anion dopant because of its ionic radius. With oxygen Very similar. Compared with metal cation doping, the excellent ion radius matching of F effectively reduces the lattice distortion. In addition, F is not an electrically active element, while active elements such as Al and Ga will diffuse into adjacent films at high temperatures, resulting in decreased device performance. Due to the advantages of F-doped ZnO, there are many methods for preparing F-doped ZnO, including chemical vapor deposition, spray pyrolysis, radio frequency magnetron sputtering, laser deposition and sol-gel synthesis. However, the traditional doping method makes the doping of F in ZnO very complicated and inefficient due to the lack of suitable precursors. Summary of the invention

[0004] In view of the defects of low doping amount, complex reaction and high cost in the preparation process of zinc oxide doped with impurity atoms in the prior art, the inventors have proposed a fast, efficient and high-concentration fluorine-doped zinc oxide preparation method after long-term experiments and research. This processing method can greatly increase the doping amount of F in ZnO material and has a high electron mobility. The operation is simple and convenient, and no complex chemical reaction is required. Since the electron perturbation caused by the non-metallic dopant fluorine is largely limited to the filled valence band, the scattering of the conduction band electrons is reduced, and the prepared ZnO has a high electron mobility and optical transparency. In addition, other active elements such as Al and Ga will diffuse to adjacent film layers at high temperatures, thereby reducing device performance and even damaging the device. F is an inactive element and can greatly avoid the degradation of device performance caused by diffusion. The doping concentration of F in the F-doped ZnO film prepared by femtosecond laser combined with fast annealing can exceed the solid solubility limit. This supersaturated doped semiconductor has unique advantages and excellent performance in many devices such as photodetectors, TFTs, solar cells, etc.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] A rapid, efficient, high-concentration fluorine-doped zinc oxide preparation method, characterized in that it specifically comprises the following steps:

[0007] Step 1: Select intrinsic zinc oxide material, and ultrasonically clean and dry the selected zinc oxide material;

[0008] Step 2: Place the cleaned zinc oxide sample into a vacuum chamber into which the doping gas is introduced, and fix it on the sample holder of the three-dimensional translation stage;

[0009] Step 3: After focusing the femtosecond laser, the sample surface is irradiated. The sample is placed in front of the focus of the femtosecond laser, and the laser flux is set to be greater than or equal to the ablation threshold of zinc oxide. The scanning path of the translation stage is controlled by a computer, and the shutter switch is controlled by a computer to irradiate the sample, thereby realizing the preparation of high-concentration fluorine-doped zinc oxide.

[0010] Step 4: Annealing the doped zinc oxide sample to activate the fluorine impurity atoms in the material, repair the lattice and eliminate defects, thereby obtaining high-concentration fluorine-doped zinc oxide; the zinc oxide treated through the above steps has a high impurity doping concentration on the crystal surface, the relative atomic ratio of fluorine can reach more than 9at.%, and the material has good electrical and optical properties.

[0011] Furthermore, the intrinsic zinc oxide material selected in step 1 is an intrinsic zinc oxide single crystal or an intrinsic zinc oxide thin film.

[0012] Furthermore, the preparation method of the intrinsic zinc oxide material selected in step 1 is a hydrothermal method, a vapor phase method, a melt growth method, a molecular beam epitaxy method, a pulsed laser deposition method, a sol-gel method or a magnetron sputtering method.

[0013] Furthermore, the solvent used for ultrasonic washing in step 1 is acetone.

[0014] Furthermore, the drying process in step 1 is drying with nitrogen.

[0015] Furthermore, the doping gas in step 2 may be sulfur hexafluoride, carbon tetrafluoride, nitrogen trifluoride or a mixture of two or three of the above gases.

[0016] Furthermore, in step 3, the sample is placed 2-10 mm in front of the focus of the femtosecond laser.

[0017] Furthermore, the annealing treatment in step 4 is rapid thermal annealing, the annealing time is 10s-20min, and the annealing temperature is 100°C-800°C.

[0018] Beneficial effects:

[0019] 1. The present invention provides a fast, efficient, high-concentration fluorine-doped zinc oxide preparation method, which has the characteristics of simple process, no need for complex chemical reactions, easy control, fast doping speed, and high doping concentration. The doping amount of F can be controlled by regulating the gas pressure containing the doping element gas, and the doping depth can be controlled by regulating the femtosecond laser energy flow.

[0020] 2. The doping area is controllable. By controlling the scanning path of the three-dimensional translation stage by computer, the doping area from micrometer scale to centimeter scale can be achieved. The scanning shape can be a one-dimensional point, a two-dimensional line or an arbitrary three-dimensional shape.

[0021] 3. The present invention prepares a high-concentration F-doped ZnO thin film material for the first time, with the F-doping amount reaching more than 9at.%; the present invention adopts femtosecond laser for doping. Since the instantaneous power of the femtosecond laser is extremely high and the action time with the material is extremely short, the material cools down very quickly after the action. A large number of doping atoms can be locked in the zinc oxide lattice at the moment of processing, which greatly improves the solid solubility of the doping atoms in ZnO.

[0022] 4. The present invention anneals the sample after femtosecond laser doping, the lattice of the sample is repaired, the defects are reduced, and the doping atoms are activated, and the sample has higher mobility, carrier concentration and transparency.

[0023] 5. The F-doped ZnO thin film material prepared by the preparation method of the present invention has a laser-induced periodic micro-nano structure on its surface, so that the film interference effect is greatly eliminated, and the transmittance of the film in the visible light range is increased to more than 90%.

[0024] 6. Using the inactive element fluorine as a dopant for ZnO can prevent impurities from diffusing into adjacent layers, thus avoiding the degradation of device performance.

[0025] 6. This method is not only applicable to the doping of F elements in ZnO, but also to the high-concentration doping of other semiconductor materials. By changing the type of gas in the vacuum chamber, the doping effect of different elements can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a schematic flow chart of a method for preparing a high-concentration F-doped ZnO thin film obtained in Example 1;

[0027] Figure 2 is a scanning electron microscope image of the high-concentration F-doped ZnO film obtained in Example 1;

[0028] Figure 3 It is the optical transmittance spectrum of the high-concentration F-doped ZnO film and the intrinsic ZnO film obtained in Example 1. The illustration is the actual image of the high-concentration F-doped ZnO film taken by a mobile phone. The concave area in the middle is the laser doping area.

[0029] Figure 4 is the energy dispersive spectrometer (EDS) spectrum of the high-concentration F-doped ZnO film obtained in Example 1, and the inset is the atomic percentage;

[0030] Figure 5 3 is an X-ray photoelectron spectroscopy (XPS) graph of the F 1s peak of the high-concentration F-doped ZnO thin film obtained in Example 1.

[0031] Figure 61 is the X-ray diffraction (XRD) spectrum of the high concentration F-doped ZnO film and the intrinsic ZnO film obtained in Example 1. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In addition, the scope of protection of the present invention should not be limited to the following specific structures or components or specific parameters.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0034] The present invention utilizes femtosecond laser irradiation of a zinc oxide sample placed in a doped gas to incorporate atoms in a large number of gas molecules into the zinc oxide lattice. The specific process is as follows: after the laser irradiates the zinc oxide sample, the sample surface will melt and ablate. At the same time, there is a certain probability that the gaseous molecules in the environment will be dissociated by the high-energy femtosecond laser and diffuse into the liquid-phase zinc oxide melted on the surface. Since the heat-affected zone of the femtosecond laser is small, a huge temperature difference will be formed between the molten layer on the surface of the zinc oxide and the substrate, so that the surface molten layer can be quickly resolidified. Since the impurity concentration in the surface of the liquid phase material after laser irradiation is not limited by the solid solubility, the resolidification speed is fast enough, and the solute in the liquid phase resolidification layer cannot fully diffuse outward, which will break the solute migration balance at the solid-liquid interface, resulting in the impurity atoms not having time to diffuse and being fixed in the zinc oxide lattice to form high-concentration doping. The doped sample is then annealed to repair the lattice defects through thermal relaxation and activate the impurity atoms. The present invention can achieve high-concentration doping of non-metallic fluorine elements in zinc oxide, avoid disturbance of the conduction band, and obtain samples with high carrier mobility, carrier concentration and transparency while ensuring a high doping amount.

[0035] In order to explain the technical means and effects of the present invention in more detail, a fast, efficient and high-concentration fluorine-doped zinc oxide preparation method proposed by the present invention is described in detail with reference to examples.

[0036] Example 1

[0037] A rapid, efficient, high-concentration fluorine-doped zinc oxide preparation method comprises the following steps:

[0038] In the first step, a zinc oxide film grown by magnetron sputtering was selected, the substrate was SiO2, and its specifications were 1.5×1.5×1cm 3 ; Place it in an acetone solution for ultrasonic cleaning for 10 minutes, then take it out and blow it dry with nitrogen.

[0039] In the second step, the cleaned sample is placed on a three-dimensional translation stage in the vacuum chamber. Figure 1 As shown, the chamber door is closed, the vacuum is evacuated to below 5Pa, and then SF6 gas is filled to 2 / 3 atmospheric pressure. The vacuum is evacuated again to below 5Pa, and then SF6 gas is filled to 2 / 3 atmospheric pressure again. This is repeated five times to ensure the purity of SF6 in the chamber.

[0040] In the third step, the femtosecond laser has a pulse width of 120fs, a central wavelength of 800nm, and a repetition rate of 1kHz. It first passes through a half-wave plate and a Glan Taylor prism to regulate the laser energy flux, and then is focused on the sample through a 50cm lens. The sample is then adjusted to be 2mm in front of the laser focus, and the laser energy flux is set to 7kJ / m 2 , open the shutter to perform femtosecond laser doping, such as Figure 1 As shown; the translation stage moves 1 cm along the X-axis, then moves 25 microns in the Y-direction, and then moves in the opposite direction along the X-axis to scan line by line. The shape and size of the scan can be controlled by a computer connected to the translation stage; after the scan is completed, the chamber is evacuated, and then nitrogen is introduced to 2 / 3 of the atmospheric pressure, and then evacuated again. After repeating 3 times, nitrogen is filled to the standard atmospheric pressure for the last time, and the chamber cover is opened to take out the sample; Figure 2 This is a scanning electron microscope image of the surface of a zinc oxide thin film sample after femtosecond laser scanning. A uniform periodic stripe structure is produced on the surface. Figure 3 This is the optical transmittance spectrum of the high-concentration F-doped film. Compared with the intrinsic ZnO film, the film interference effect is effectively suppressed due to the formation of a periodic stripe structure on the surface of the sample after femtosecond laser irradiation. Figure 3 As shown in the inset, the uniformity and transmittance of the film in the visible light range are effectively improved. In the range of 400-900nm, the average optical transmittance is increased from 83% to more than 90%; Figure 4 This is the EDS spectrum of the ZnO sample doped with F by femtosecond laser. An obvious F doping peak can be observed. The inset shows the atomic percentages. The relative atomic ratio of F can reach 9.52%. In addition, the XPS test of the sample can detect the F 1s peak at 684.7 eV, as shown in Figure 2. Figure 5 As shown in Figure 3, this peak corresponds to the Zn-F bond, indicating that there are sufficient number of substitutional F atoms in the ZnO lattice.

[0041] In the fourth step, the ZnO film is placed in a rapid thermal annealing device for annealing at 600°C for 10 min. Its crystal structure is given by the XRD spectrum, as shown in Figure 6 Compared with the intrinsic ZnO film, the (002) diffraction peak in the XRD spectrum after annealing is significantly enhanced, which indicates that annealing can repair defects and improve the lattice quality. In addition, the Hall test of the high concentration F-doped ZnO film shows that the Hall mobility can reach 20 cm 2 V -1 s -1 The above effectively solves the problem of low mobility caused by cation doping.

[0042] The above examples are only preferred specific embodiments of the present invention, but are not intended to limit the embodiments, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. It can be understood by a person of ordinary skill in the art that various modifications can be made in form and detail without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A rapid, efficient, high-concentration fluorine-doped zinc oxide preparation method, characterized in that: The specific steps include: Step 1: Select intrinsic zinc oxide material, and ultrasonically clean and dry the selected zinc oxide material; Step 2: Place the cleaned zinc oxide sample into a vacuum chamber into which a doping gas is introduced, and fix it on a sample holder of a three-dimensional translation stage; the doping gas is sulfur hexafluoride, carbon tetrafluoride, nitrogen trifluoride or a mixture of two or three of the above gases; Step 3: After focusing the femtosecond laser, the sample surface is irradiated. The sample is placed 2-10 mm in front of the focus of the femtosecond laser. The laser flux is set to be greater than or equal to the ablation threshold of zinc oxide. The scanning path of the translation stage is controlled by a computer. At the same time, the shutter switch is controlled by a computer to irradiate the sample, thereby realizing the preparation of high-concentration fluorine-doped zinc oxide. Step 4: annealing the doped zinc oxide sample, wherein the annealing is rapid thermal annealing, the annealing time is 10s-10min, and the annealing temperature is 600-800°C, so as to activate the fluorine impurity atoms in the material, repair the lattice, and eliminate defects, thereby obtaining high-concentration fluorine-doped zinc oxide; After the zinc oxide is processed through the above steps, the impurity doping concentration on the crystal surface is very high, the relative atomic ratio of fluorine can reach more than 9at.%, and the material has good electrical and optical properties.

2. A fast, efficient, high-concentration fluorine-doped zinc oxide preparation method according to claim 1, characterized in that: The intrinsic zinc oxide material selected in step 1 is an intrinsic zinc oxide single crystal or an intrinsic zinc oxide thin film.

3. A method for preparing a fast, efficient, high-concentration fluorine-doped zinc oxide according to claim 1, characterized in that: The preparation method of the intrinsic zinc oxide material selected in step 1 is a hydrothermal method, a gas phase method, a melt growth method, a molecular beam epitaxy method, a pulsed laser deposition method, a sol-gel method or a magnetron sputtering method.

4. A fast, efficient, high-concentration fluorine-doped zinc oxide preparation method according to claim 1, characterized in that: The solvent used for ultrasonic washing in step 1 is acetone.

5. A fast, efficient, high-concentration fluorine-doped zinc oxide preparation method according to claim 1, characterized in that: The drying process in step 1 is drying with nitrogen gas.

Citation Information

Patent Citations

  • Preparation method of nitrogen-fluorine co-doped zinc oxide thin film

    CN105671507A

  • Preparation method for supersaturated doping of semiconductor surface and maintaining lattice structure thereof

    CN109378269A

  • No title available

    GB1225722A